Acclimation of apple peel to light and temperature and the effect thereof on red colour development and tolerance to sunburn - Barasu, Prince Dogbeda (Stellenbosch : Stellenbosch University, 2017)
Thesis (MScAgric)--Stellenbosch University, 2017.